2015
DOI: 10.1002/hyp.10447
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate fluctuations at the water table: implications for recharge processes and solute transport in the Chalk aquifer

Abstract: This study investigates fluctuations in nitrate concentration at the water table to improve understanding of unsaturated zone processes in the Chalk aquifer. Sampling was conducted using a novel multi-level sampler during periods of water table rise over five years. The sampler allowed near continuous sampling at a vertical resolution of 0.05 m. Nitrate concentration increased as the water table seasonally recovered, with similar interannual trends with depth. The rising water table activated horizontal fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…For soil‐enriched solutes, diffuse percolation of soil water to small fractures in depression increases the availability of solutes in small fracture water (Sorensen et al, 2015; Yue et al, 2019). In addition, higher water level in conduits at the beginning of a flood can lead water flux with high concentrations (showing in Figure 7) from conduits to small fractures, known as the ‘bidirectional exchange’ between conduit and small fracture in karst critical zone (Chen et al, 2018; Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For soil‐enriched solutes, diffuse percolation of soil water to small fractures in depression increases the availability of solutes in small fracture water (Sorensen et al, 2015; Yue et al, 2019). In addition, higher water level in conduits at the beginning of a flood can lead water flux with high concentrations (showing in Figure 7) from conduits to small fractures, known as the ‘bidirectional exchange’ between conduit and small fracture in karst critical zone (Chen et al, 2018; Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For NO − 3 , El Gaouzi et al (2013) observed concentrations between 34 and 49 mg l −1 in boreholes or springs in the Paris Basin. Sorensen et al (2015) found nitrate concentrations ranging from 30 to 60 mg l −1 for the Chalk aquifer in the UK. For pesticides, Baran et al (2008) At Saint-Martin-le-Noeud, the concentrations of nitrate, atrazine and DEA vary spatially along the quarry both in lakes and percolating water.…”
Section: Contaminant Transport and Degradationmentioning
confidence: 99%
“…129 Moreover, the concentrations of NO 3 − increased with an uplifted groundwater table in the U.K. over 5 years, and researchers implied that varied NO 3 − concentrations were also determined by fracture displacement and the amplitude and frequency of GTF. 130 The variation of groundwater physicochemical properties, such as DO, pH, and E h , caused by GTF significantly influences the migration and transformation of nitrogenous compounds (NO 3 − , NH 4 + , and NO 2 − ) in unsaturated soil and saturated aquifers. In a case study in the Luoyang area, China, the nitrate nitrogen concentration increased with a decreasing groundwater table, whereas the ammonium nitrogen concentration decreased because of the variations in the physicochemical properties of the soil and groundwater.…”
Section: Impacts Of Gtf On the Migration Transformation And Retention...mentioning
confidence: 99%